Economic diplomacy of the Czech Republic - Pyszko, Marek (2018)
The aim of this thesis is to analyse the Economic diplomacy of the Czech Republic, using both comparative and analytical approach based on analysis of its current structure and functionality. The emphasis is put on the representation of the Czech economic diplomacy abroad and the problems of its duality within Economic and Commercial Section of the embassies (representing Ministry of Foreign Affairs) and the CzechTrade agency (coordinated by Ministry of Industry and Trade). The thesis deals with Czech economic diplomacy, the development, models and export strategies as well as all actor involved. The economic diplomacy of the Czech Republic is also compared with other countries such as Hungary, Estonia, Slovakia, Finland or Portugal and Austria, with the emphasis on the models and strategy of governance of economic diplomacy.